Expression of Bacillus thuringiensis toxin Cyt2Ba in the entomopathogenic fungus Beauveria bassiana increases its virulence towards Aedes mosquitoes - Deng, Sheng-Qun; Zou, Wei-Hao; Li, Dong-Liang; Chen, Jia-Ting; Huang, Qiang; Zhou, Li-Juan; Tian, Xiao-Xue; Chen, Yi-Jun; Peng, Hong-Juan (PLoS neglected tropical diseases, 2019)
The entomopathogenic fungus Beauveria bassiana has been widely used to kill mosquito larvae and adults in the laboratory and field. However, its slow action of killing has hampered its widespread application. In our study, the B. bassiana fungus was genetically modified to express the Bacillus thuringiensis (Bt) toxin Cyt2Ba to improve its efficacy in killing mosquitoes. The efficacy of the wild type (WT) of B. bassiana and a transgenic strain expressing Cyt2Ba toxin (Bb-Cyt2Ba) was evaluated against larval and adult Aedes mosquitoes (Aedes aegypti and Aedes albopictus) using insect bioassays. The Bb-Cyt2Ba displayed increased virulence against larval and adult Aedes mosquitoes compared with the WT: for Ae. aegypti adults, the median lethal time (LT50) was decreased by 33% at the concentration of 1× 108 conidia/ml, 19% at 1× 107 conidia/ml and 47% at 1× 106 conidia/ml. The LT50 for Ae. albopictus adults was reduced by 20%, 23% and 29% at the same concentrations, respectively. The LT50 for Ae. aegypti larvae was decreased by 42% at 1× 107 conidia/ml and 25% at 1× 106 conidia/ml, and that for Ae. albopictus larvae was reduced by 33% and 31% at the same concentrations, respectively. In addition, infection with Bb-Cyt2Ba resulted in a dramatic reduction in the fecundity of Aedes mosquitoes. In conclusion, our study demonstrated that the virulence of B. bassiana against mosquitoes can be significantly improved by introducing the Bt toxin gene Cyt2Ba into the genome to express the exogenous toxin in the fungus. The transgenic strain Bb-Cyt2Ba significantly reduced the survival and fecundity of Ae. aegypti and Ae. albopictus compared with the WT strain, which suggested that this recombinant B. bassiana has great potential for use in mosquito control.